Assessment of the Knowledge and Awareness Levels of Dentists Regarding_x000D_ Prophylaxis for Infective Endocarditis - (:unkn) unknown (My University, 2019)
Aim: Infective endocarditis (IE) is a serious heart disease with high mortality and morbidity. Antibiotic prophylaxis is recommended for patients at risk of infective endocarditis before dental procedures. This Turkish online descriptive survey aimed to evaluate the knowledge and awareness levels of dentists and dental studentsregarding antibiotic prophylaxis for patients at risk of infective endocarditis.Method: Data on participants’ demographics and responses regarding dental treatments and heart diseasesrequiring prophylaxis as well as antibiotic dosage, duration, and administration time were collected betweenFebruary 1 and June 30, 2016 in Turkey. For each correct answer one point was given. A score of >4 was consideredsuccessful.Results: In total, 584 dentists and 199 dental students participated in the questionnaire survey. The rate of ad-ministration of antibiotic prophylaxis against infective endocarditis was found as 92.59%. Overall success ratesof dental procedures requiring prophylaxis and knowledge regarding heart diseases were 90.3% and 72.6%,respectively. Knowledge levels regarding the use of antibiotic prophylaxis for heart diseases and antibiotic do-sage and duration were greater in women, those with ≤5 years of professional experience, dentists, and thoseworking at dental faculties (p<0.05). Dentists with ≤5 years of professional experience had greater levels ofawareness about dental procedures requiring prophylaxis than those with >5 years of experience (p<0.001).Conclusion: Given their poor knowledge of antibiotic prophylaxis against infective endocarditis, once again ithas been revealed that dentists should receive in-service training to keep up with current practices.

Amaç: İnfektif endokardit (İE), yüksek mortalite ve morbiditeye sahip ciddi bir kalp hastalığıdır. İE riski taşıyan_x000D_ hastalara dental girişim öncesinde antibiyotik profilaksisi önerilmektedir. Online uygulanan tanımlayıcı nitelikteki_x000D_ bu anket çalışmasının amacı, İE gelişme riski bulunan hastalara diş hekimlerin ve diş hekimliği öğrencilerinin anti-_x000D_ biyotik profilaksisi uygulama konusundaki bilgi ve farkındalık düzeylerini değerlendirmektir._x000D_ Yöntem: Profilaksi gerektiren dental girişimler ve kalp hastalıkları, profilakside uygulanan antibiyotiklerin dozu,_x000D_ süresi ve uygulama zamanı ile ilgili sorulara verilen yanıtlar ile birlikte katılımcıların demografik bilgilerini içe-_x000D_ ren anket verileri 1 Şubat-30 Haziran 2016 tarihleri arasında toplanmıştır. Her doğru cevaba bir puan verilmiş_x000D_ ve dört puan üstü başarılı olarak kabul edilmiştir._x000D_ Bulgular: Toplamda 584 diş hekimi ve 199 diş hekimliği öğrencisi ankete katılmıştır. İE profilaksisi uygulama oranı_x000D_ %92,6 saptanmıştır. Profilaksi gerektiren dental prosedürler ve kalp hastalıkları ile ilişkili sorularda genel başarı oranı_x000D_ sırasıyla %90,3 ve %72,6 olarak bulunmuştur. Kadınların, beş ve beş yıldan daha az deneyimi olan diş hekimlerin ve_x000D_ diş hekimliği fakültelerinde çalışanların profilaksi gerektiren kalp hastalıkları, antibiyotik dozu ve uygulama süresi ile_x000D_ ilgili bilgi düzeyleri daha yüksek saptanmıştır (p<0,05). Beş ve beş yıldan daha az deneyimli diş hekimlerinin profilaksi_x000D_ gerektiren dental prosedür konusundaki farkındalık düzeyi beş yıldan fazla deneyim sahibi olanlara göre daha faz-_x000D_ ladır (p<0,001)._x000D_ Sonuç: Diş hekimlerinin İE profilaksisi uygulama konusunda bilgi düzeylerinin düşük saptanması, diş hekimlerinin_x000D_ güncel gelişmeleri takip etmeleri için hizmet içi eğitimlerin gerekliliği bir kez daha ortaya koymuştur.
Diş Hekimlerinin İnfektif Endokardit Profilaksisi Hakkında Bilgi ve Farkındalık Düzeylerinin Değerlendirilmesi